Criminological Study on Money Politics Crime in Elections: An Alternative Solution - Taksir, Yuli Rahayu; Satria, Hariman (Faculty of Law, Universitas Pekalongan, 2024)
The massive of money politics offence can be seen by data from the Indonesian Police and Bawaslu that in the 2019 Election there were 35 cases of money politics spread across 13 provinces. What is surprising is the research results from LIPI that more than 30% of voters believe that money politics is part of the democratic process so that it becomes something natural. In this context, there is a kind of urgency that forces a serious study of the money politics offences. The problem of this research is how money politics offences when viewed from a criminological perspective? This study uses a socio-legal research method, namely looking at legal problems with an interdisciplinary theoretical and methodological approach. The results of the study are as follows: (1) the positive paradigm refers to the consensus perspective, viewing the money politics offences as an action that is contrary to the consensus that has been agreed upon between the community represented by the legislature and executive. (2) the interactionist paradigms which departs from a pluralist perspective, viewing money politics offences as a reaction from society in the form of stigmatization of perpetrators of money politics. (3) the socialist paradigm which refers to the conflict perspective. That the money politics offences is seen as a disagreement of the perpetrators with the provisions that have been ratified by the state, in this case the Election Law. When connected with criminology theory, money politics offences is related to two theories, namely the anomie theory and the theory of social ties. It is recommended that in making policies regarding the Election, the government and legislation need to be based on criminology findings regarding the causes and effects of money politics offences